Interaction for learning in the Anglophone university classroom: Mastering interactional challenges through reflective practice - Dippold, Doris (Journal of Academic Language and Learning, 2013)
In the internationalised classroom of the Anglophone world, tutors as well as students face the challenge of negotiating the norms of classroom interaction which frequently remain opaque, potentially leading to feelings of alienation and lost learning opportunities. After reviewing the literature on academic classroom talk in international and multilingual/multicultural settings, this paper uses episodes from one UK higher education classroom and the retrospective comments by the classroom tutor to discuss the challenges faced by students and tutors in today’s “internationalised” Anglophone university. It ends by suggesting that the principle of “reflective practice”, if implemented in staff development courses and in courses for all members of the classroom community, can train students to use spoken academic language more effectively in the internationalised Anglophone university. The paper further hopes to be able to bring together the discourses on internationalisation used in applied linguistics and education studies in the interest of more intensive collaboration between the two fields of research.